Deeping into Effective Teaching Strategies in Developing Vocabulary of English as a Foreign Language - Ediwarman, Ediwarman; Pahamzah, John (Journal of Linguistics, Literacy, and Pedagogy, 2024)
The purpose of this article is to conduct critical reviews of vocabulary teaching strategies that have been effectively used in English classroom. The data obtained is contained in the site Google Scholar with the topic Method for Teaching Vocabulary in English. The result of the analysis article shows some effective strategies for teaching English vocabularies, such as teaching English vocabulary using drama, flashcards, movies, animation videos, and crosswords.